Where Does Interventional Radiology Fit in with Trauma Management Algorithm? - Pillai, A. S.; Srinivas, S.; Kumar, G.; Pillai, A. K. (Seminars in Interventional Radiology, 2021)
Trauma is a major cause of death in the United States, particularly in the younger population. Many traumatic deaths, as well as major morbidity, occur secondary to uncontrolled hemorrhage and eventual exsanguination. Interventional radiology plays a major role in treating these patients, and interventional techniques have evolved to the point where they are an integral part of treatment in these critically ill patients. This article reviews the role of interventional radiology in the treatment algorithms for traumatic injury sponsored by major societies and associations.
Keywords: trauma; hemorrhage; embolization; algorithm; interventional radiology